Endeavor of Iontronics: From Fundamentals to Applications of Ion‐Controlled Electronics. Issue 25 (5th June 2017) - Bisri, Satria Zulkarnaen; Shimizu, Sunao; Nakano, Masaki; Iwasa, Yoshihiro
Abstract : Iontronics is a newly emerging interdisciplinary concept which bridges electronics and ionics, covering electrochemistry, solid‐state physics, electronic engineering, and biological sciences. The recent developments of electronic devices are highlighted, based on electric double layers formed at the interface between ionic conductors (but electronically insulators) and various electronic conductors including organics and inorganics (oxides, chalcogenide, and carbon‐based materials). Particular attention is devoted to electric‐double‐layer transistors (EDLTs), which are producing a significant impact, particularly in electrical control of phase transitions, including superconductivity, which has been difficult or impossible in conventional all‐solid‐state electronic devices. Besides that, the current state of the art and the future challenges of iontronics are also reviewed for many applications, including flexible electronics, healthcare‐related devices, and energy harvesting. Abstract : Iontronics bridges the two worlds of electronics and ionics at the interface of electronic conductors and ionic conductors. Recent progress in this emerging field is highlighted from both the fundamental material science aspects and application perspectives. This includes the discovery of new physics and of the emerging functionality of ion‐controlled electronics for thermoelectrics, neuromorphic devices, and flexible electronics.